COVID-19-Associated Pulmonary Aspergillosis: A Single-Center Experience in Central Valley, California, January 2020–March 2021 - Sivasubramanian, Geetha; Ghanem, Hebah; Maison-Fomotar, Michele; Jain, Ratnali; Libke, Robert (Journal of fungi (Basel), 2021)
Reports of coronavirus disease 2019 (COVID-19)-associated pulmonary aspergillosis (CAPA) have been widely published across the world since the onset of the pandemic with varying incidence rates. We retrospectively studied all patients with severe COVID-19 infection who were admitted to our tertiary care center′s intensive care units between January 2020 and March 2021, who also had respiratory cultures positive for Aspergillus species. Among a large cohort of 970 patients admitted to the ICU with severe COVID-19 infections during our study period, 48 patients had Aspergillus species growing in respiratory cultures. Based on the 2020 European Confederation of Medical Mycology and the International Society for Human and Animal Mycology (ECMM/ISHAM) consensus criteria, 2 patients in the study had proven CAPA, 9 had probable CAPA, and 37 had possible CAPA. The incidence of CAPA was 5%. The mean duration from a positive COVID-19 test to Aspergillus spp. being recovered from the respiratory cultures was 16 days, and more than half of the patients had preceding fever or worsening respiratory failure despite adequate support and management. Antifungals were given for treatment in 44% of the patients for a mean duration of 13 days. The overall mortality rate in our study population was extremely high with death occurring in 40/48 patients (83%).